Pengaruh Struktur Modal, Kinerja Keuangan, dan Kebijakan Dividen terhadap Nilai Perusahaan (Studi pada Perusahaan Property and Real Estate yang terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Putri Ayu Khoriah; Ronny Malavia Mardani; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was conducted to determine the effect of Capital Structure, Financial Performance and Dividend Policy on Firm Value (a study of the Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period). This study uses explanatory research with a quantitative approach. The population in this study were 65 property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Determination of the sample based on purposive sampling method obtained a number of 7 companies. The analysis was carried out using secondary data and multiple linear regression analysis methods. The results of this study prove that: 1) capital structure proxied by Debt to Equity Ratio has a positive and significant effect on firm value, 2) Financial performance as proxied by Return on Equity has a positive and significant effect on firm value, 3) Dividend policy proxied by Dividend Yield has an insignificant negative effect on the value of the company. Keywords: Capital Structure, Financial Performance, Dividend Policy, Firm Value.